A high‐throughput energy‐dispersive tender X‐ray spectrometer for shot‐to‐shot sulfur measurements. (2nd April 2019) - Abraham, Baxter; Nowak, Stanislaw; Weninger, Clemens; Armenta, Rebecca; Defever, Jim; Day, David; Carini, Gabriella; Nakahara, Kazutaka; Gallo, Alessandro; Nelson, Silke; Nordlund, Dennis; Kroll, Thomas; et al.
Abstract : An instrument for photon‐in photon‐out spectroscopy at XFELs in the energy range between soft and hard X‐rays is presented. Abstract : An X‐ray emission spectrometer that can detect the sulfur K α emission lines with large throughput and a high energy resolution is presented. The instrument is based on a large d ‐spacing perfect Bragg analyzer that diffracts the sulfur K α emission at close to backscattering angles. This facilitates the application of efficient concepts routinely employed in hard X‐ray spectrometers towards the tender X‐ray regime. The instrument described in this work is based on an energy‐dispersive von Hamos geometry that is well suited for photon‐in photon‐out spectroscopy at X‐ray free‐electron laser and synchrotron sources. Comparison of its performance with previously used instrumentation is presented through measurements using sulfur‐containing species performed at the LCLS. It is shown that the overall signal intensity is increased by a factor of ∼15. Implementation of this approach in the design of a tender X‐ray spectroscopy endstation for LCLS‐II is also discussed.